(untitled) (Bangladesh Journal of Zoology, 2018)
The purpose of the present study was to compare results of saline, iodine, and KOH wet mount preparations executed on each of 1116 stool samples from patients attending ICDDR,B clinical pathology laboratory was compared. Ascaris lumbricoides was most prevalent helminth (3.67%) found in KOH wet mount preparation. The protozoan parasites (9.59%) were more prevalent than helmiths (8.24%) and Giardia sp (4.03%) shows the higher infection found by KOH wet mount preparation. Females are more infected by parasites than males found in observations by all the three methods (saline, iodine and KOH wet mount preparation). It was also observed that the young (1- 10 years) were more infected than older age group (above 51). In seasonal variation, parasitic infestation was higher during May (27%) and the prevalence was lower in December (10%). KOH was found to be effective in destroying the faecal debris, faecal mass and other artifacts without affecting many of the parasitic ova, cysts and larvae in the stool smears. KOH for wet mount smear in examining the stool samples for detection of intestinal helminths may be routinely used which is simple, cost-effective and could be afforded in resource poor setting. Bangladesh J. Zool. 45(2): 159-170, 2017